The Inclusive and the Exclusive in Mongolian - Domii , Tumurtogoo (Acta Mongolica, 2006)
A phenomena of the inclusive was first introduced to the Altaic linguistics when a famous turkologist O. Bohtlink’ had considered the structure of the first-personal plural pronoun in Yakut biz “we” as consisting of the components bi + si “J + уди”.